The Texas stories of Nelson Algren - Algren, Nelson 1909-1981 (Univ. of Texas Pr., 1995)
Twelve stories on the author's hobo days in Texas where he searched for work during the 1930s depression and was jailed for stealing. In one story he writes, "God help you if you run and God help you if you fight; God help you if you're broke and God help you if you're black."
Keywords: Alltag, Brauchtum; Texas -- Social life and customs -- Fiction